Effects of Using Computer Games as an Instructional Tool on Third Grade Students’ Acquisition of Higher Order Thinking Skills - Al Abbadi , Hamed (Jordan Journal of Educational Sciences, 2005)
The purpose of this study is to investigate the effect of computer games as an instructional tool on third grade students’ acquisition of higher order thinking skills. Three instructional computer games that cover the content of three lessons in Arabic, Mathematics and Science textbooks were used. Thirtytwo students served as the experimental group and were taught via computer games, and 31 students served as the control group and were taught the same content without using computer games. Subjects were all chosen from a public school in Irbid in the northern part of Jordan. The target higher order thinking skills were analysis, synthesis, and evaluation, assessed by an achievement test designed for this purpose. The results of the study revealed significant differences among students in the acquisition of the three levels of higher order thinking skills in favor of the experimental group, indicating a significant effect of computer games on acquiring higher order thinking skills.